Human Resources Transformation in Medical at Sidoarjo Citra Medika Hospital Research - Haryawan, Beny; Basuni, Basuni; Kusumaningrum, Dyah Ayu Dwi (Journal of Applied Business, Taxation and Economics Research, 2024)
Research Aims The human resource transformation (SDM) that has taken place in the medical manufacturing sector has resulted in the formation of capabilities that are both innovative and effective, leading to an increase in the quality of services. Research is being conducted on Citra Medika Hospital in Sidoarjo because of its significant role in the Indonesian population's health. When it comes to the management of SDM, medical imaging hospitals face a unique challenge, particularly when it comes to integrating advances in medical technology with rapidly expanding patient service requirements. Citra Medika Hospital was selected because of its reputation as a forward-thinking hospital in medical technology and the management of the SDM. Furthermore, the continuous occurrence of academic degree fraud constitutes unethical behavior, which is why the decision was made to select this hospital. The purpose of this study is to gain an understanding of the internal and external dynamics that impact the management of SDM in the medical imaging hospital, as well as the strategies utilized to confront and manage changes of this nature. Using qualitative methods and descriptive analysis, this research methodology will be developed to investigate and comprehend human resources transformation at the Citra Medika Hospital in Sidoarjo